An Immersive Speaking Program in Kampung Inggris: Teaching Practices and Learner Difficulties - Muhammad Ridho Pangestu; Siti Azizah Nurhalimah Rais; Yanti Rosalinah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Immersive English programs have increasingly been seen as a practical way to boost speaking fluency among EFL learners in Indonesia. Even so, little is known about how speaking is taught in these programs and what difficulties learners encounter, especially from an instructor’s point of view. This study explores how an instructor with seven years of teaching experience delivers speaking instruction in a one-month immersive program in Kampung Inggris and describes the challenges learners typically face during the process. Using a descriptive qualitative approach, data were collected through a WhatsApp interview and analyzed thematically based on Braun and Clarke’s (2006) framework. The findings show that the instructor relied heavily on continuous speaking practice through pair-work, individual presentations, performance-based activities, and playful routines like rap-style ice breaking to lower anxiety and encourage spontaneous speech. However, two persistent issues remained: limited vocabulary and low confidence. According to the instructor, the English-only environment and punishment system helped learners gradually overcome these obstacles. This study adds to the growing body of research on immersive learning by highlighting how teaching practices shape the speaking experience in an offline setting. The findings point to the need for carefully structured speaking instruction that balances pressure, support, and repetition to help learners perform confidently in English.